Effects of direct oral anticoagulants vs. vitamin K antagonists on acute kidney injury in patients with atrial fibrillation: A systematic review - Chengfa Ren; Yudan Zhao; Dehui Liu (Frontiers in Cardiovascular Medicine, 2023)
BackgroundPatients with atrial fibrillation (AF) are routinely prescribed oral anticoagulants to prevent thromboembolism. Concerns regarding the efficacy and safety of oral anticoagulants, such as vitamin K antagonists (VKA) and direct oral anticoagulants (DOACs), arise for patients with non-valvular atrial fibrillation (NVAF) because of their widespread use in clinical practice. Even though there have been an abundance of studies on this topic, it is still not clear if DOAC users with NVAF have a lower risk of acute kidney injury (AKI) than warfarin users.Methods and resultsWe conducted electronic searches in PubMed, Embase, and the Cochrane Library to identify relevant studies for this systematic review. We included randomized clinical trials and observational studies that reported on the incidence rate, hazard ratio (HR), and 95% confidence interval (95% CI) of AKI in patients using oral anticoagulants. This systemic review included six observational studies and four randomized clinical trials (RCT). The overall results showed that DOACs were associated with a lower AKI risk than warfarin. However, for NVAF patients with severe renal dysfunction, DOACs may not have a reduced risk of AKI compared to warfarin.ConclusionThe overall results suggest that, except for edoxaban, patients using DOACs may experience a reduced risk of AKI. However, it is uncertain whether this is also the case for patients with severe renal dysfunction. Further research is needed to confirm the effect of DOACs on this population.